Kinesics As A Form of Non Verbal Communication: A Textual Analysis Of The Holy Quran - OTHMAN, MOHD ALA-UDDIN; ISMAIL, ZAWAWI; ZAID, CHE MOHD; MAJID, MOHAMMAD RUSDI AB; HALIAS, NORDIN; JUSOH, ZAILANI; NASIR, MOHD SHAHRIZAL (The journal of contemporary issues in business and government, 2021)
Al-Quran is a holy book revealed to the Moslems as a guidance. The revelation is very comprehensive, covering all aspects of life. As such, it is no wonder that to date, it has attracted a lot of interests from scholars who have tirelessly been analyzing the contents of the book to gain better understanding of it. One discipline that has widely been investigated is communication, specifically non verbal. This article is written based on a qualitative study undertaken to understand one component of non verbal communication, that is, kinesics. The study was conducted using content analysis method whereby verses in the Quran were analysed to examine the use of kinesics as a form of communication. The findings revealed that in al Quran, kinesics can generally be categorized into four namely 1) arm movements 2) head movements 3) leg movements, and 4) body postures including sitting down, lying down, bowing, and prostration. The study has proven the presence of kinesics as a form of non verbal communication as clearly explicated in Al-Quran.